Producing television agriculture program : issues and problems among Malaysian television producers. - Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Shahkat Ali, Muhamad Sham; Ramli, Nor Sabila (Science Publications, 2010)
Problem statement: One of the developing sectors in Malaysia is agriculture. Agriculture doubtlessly has assisted this country in terms of enhancing the economic level, offering a huge number of employment opportunities and uplifting the socio-economy status of the community. To ensure the sustainability of this sector to the country, we must ensure that the valuable agriculture information is continuously provided to the public and the information must be disseminated through the most effective channel. Here, television can be the mean channel. Approach: This study aimed to investigate the issues raised and problems faced by the Malaysian agriculture television program producers in producing the television agriculture programs. Data was collected using an in-depth interview among three agriculture television producers in Malaysia. The questions served as a guide,but allowed respondents freedom and flexibility in their answers. The findings were in the form of descriptive analysis. Results: Based on the analysis done, it can be concluded that the cooperation between Radio Television Malaysia and Department of Agriculture Malaysia is important to ensure the success and continuity of the agriculture programs. It was found that the agriculture programs were evaluated internally by the Radio Television Malaysia auditor and externally by AGB Nielsen. The producers also received feedback from their local and foreign audience in the form of e-mail and telephone. Human resource, transportation and financial are the main problems that need to be overcome by the producers. Conclusion/Recommendations: It is suggested that other media organizations and giant agriculture companies can join RTM in producing agriculture programs. This can aid RTM in producing more innovative agriculture programs and can attract the youth to watch the program.